2011
DOI: 10.1007/s00726-011-0939-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TiO2 on prebiotic thermal synthesis of the Gly-Gln polymer

Abstract: The role of the titanium dioxide (rutile and anatase) with and without room light on the thermal synthesis of the glycine-L-glutamine (Gly-Gln) polymer is described. The efficiency in percentage of polymerization with room light was increased in 6% in the presence of rutile and in 23% in the presence of anatase. The thermal synthesis in the molten state was carried out in the absence and presence of both oxides. In all cases, the vibrational spectra showed characteristic group frequencies corresponding to a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…[22] Because the same experimental conditions were adopted to adsorb Gly onto the other two samples, the formation of peptides on SiO 2 and TiO 2 clearly indicates that these materials exhibit catalytic activity toward the formation of poly-Gly. The catalytic activity of TiO 2 in the formation of long polypeptides was observed by Leyton et al, [21] whose work operated in a thermal polymerization regime (448-463 K) with the amino acids in the molten state. range of the Gly/TiO2 spectrum.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…[22] Because the same experimental conditions were adopted to adsorb Gly onto the other two samples, the formation of peptides on SiO 2 and TiO 2 clearly indicates that these materials exhibit catalytic activity toward the formation of poly-Gly. The catalytic activity of TiO 2 in the formation of long polypeptides was observed by Leyton et al, [21] whose work operated in a thermal polymerization regime (448-463 K) with the amino acids in the molten state. range of the Gly/TiO2 spectrum.…”
mentioning
confidence: 85%
“…The absence of reactivity in the Gly/HA indicated that the temperature reached by the system during the Gly adsorption (403 K) was insufficient to allow a thermal polymerization of the amino acids, [20,21] which would be expected in the presence of trifunctional amino acids. [22] Because the same experimental conditions were adopted to adsorb Gly onto the other two samples, the formation of peptides on SiO 2 and TiO 2 clearly indicates that these materials exhibit catalytic activity toward the formation of poly-Gly.…”
mentioning
confidence: 99%
“…The structural and spectroscopic properties of the dipeptide 2-[ [5-amino-5-oxo-2-(phenylmethoxycarbonylamino) pentanoyl] amino] acetic acid (APPA) are important for the characterization of complex mixtures of oligopeptides that contain similar fragments, which are obtained by prebiotic thermal synthesis from aminoacetic acid (glycine) and 2-amino-4-carbamoylbutanoic acid (glutamine) [1][2][3]. Also, the phenylmethoxycarbonylamino moiety forms parts of many antiretroviral therapy (ART) drugs, which are medications that prevent retroviruses, such as HIV, from making copies of themselves [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was also claimed that copolymerization of glutamic acid and glycine on alumina [33] resulted in long alternate (Gly-Glu) n polymers, and that copolymerization of glutamine and glycine on titania yielded alternate (Gly-Gln) n [34]. In the same way, mixed species with equal numbers of each amino acid were observed preferentially upon thermal activation of (Glu+Arg) on montmorillonite clay [30], but this preference for alternate polymers may be due as much to the properties of the amino acids themselves as to the influence of the surface [35].…”
Section: Polymerization Selectivity and Organizationmentioning
confidence: 99%